Comparative Assessment on Selected Physicochemical Parameters and Antioxidant and Antimicrobial Activities of Honey Samples from Selected Districts of the Amhara and Tigray Regions, Ethiopia - Mekuanint Lewoyehu; Meareg Amare (International Journal of Food Science)
The composition and properties of natural honeys differ with plant species on which the bees forage and the climatic conditions of the production areas. In Ethiopia, Amhara and Tigray are neighboring regions consisting of different agricultural activities and blossoms from different types of vegetations which may influence the natural composition and hence the properties of honey. So, the aim of the current study was to assess the quality of honey from selected districts of the two regions. In the study, 18 composited honey samples were collected from six selected districts and analyzed for selected physicochemical parameters and antioxidant and antimicrobial activities. The analyses of physicochemical parameters were carried out following standard procedures of IHC and QSAE. The antioxidant activity was determined by analyzing the RSA using DPPH while the antibacterial activities were determined by the agar well diffusion method. The moisture, ash content, electrical conductivity, pH, free acidity, reducing sugar, and sucrose content of the honey samples were found to be in the range 16.34 ± 0.26 to 19.83 ± 0.43 %, 0.08 ± 0.00 to 0.45 ± 0.03 %, 0.19 ± 0.00 to 0.89 ± 0.03 mS/cm, 3.79 ± 0.04 to 4.20 ± 0.01, 19.56 ± 1.13 to 38.11 ± 1.54 meq/kg, 62.10 ± 0.48 to 66.37 ± 0.20 %, and 1.35 ± 0.08 to 5.96 ± 0.10 %, respectively. The total phenolic content ranged from 1165.60 ± 23.45 to 1854.83 ± 10.47 mg/kg with antioxidant activity of 21.64 ± 0.26 to 36.12 ± 0.52 AEAC/100 g. The total phenolic contents showed strong correlation with RSA. Furthermore, all honey samples showed an antibacterial activity varying from 23.23 ± 0.12 to 28.84 ± 0.24 mm.